Reference values and biological factors influencing skin autofluorescence - Wolffenbuttel, Bruce H.R.; Boersma, Henderikus E.; van Waateringe, Robert; Paterson, Andrew D.; van der Klauw, Melanie M. (Frontiers in Endocrinology, 2025)
IntroductionTissue glycation, measured as skin autofluorescence (SAF) with an AGE Reader, has been associated with incident type 2 diabetes (T2D), cardiovascular disease (CVD), and CVD and cancer mortality. Validated reference intervals in healthy individuals are needed to make useful and precise risk estimations.MethodologyThis study utilises data from 82,870 participants of Western European descent in the Lifelines Cohort Study, a population-based study in the Netherlands. Reference values for SAF were established in healthy participants. Decade-specific mean SAF values were evaluated for former and current smokers, T2D, CVD, and impaired renal function. We also assessed the association of regular physical activity (PA) with SAF scores.ResultsReference values for healthy individuals were established in 8,179 men and 7,930 women between 18 and 70 years, who had never smoked, had a BMI below 35 kg/m2, and did not meet the metabolic syndrome criteria. Linear regression analyses yielded the following prediction for SAF, separately by sex: in males, SAF predicted = (0.0191 × age) + 1.038, and in females, SAF predicted = (0.0188 × age) + 0.994. Current smokers had consistently higher SAF scores. There was a progressively higher SAF with a higher number of pack-years of smoking in each age decade, in both sexes. For each decade, both people with T2D and CVD had significantly higher SAF values compared to healthy individuals. The same applied to participants with impaired renal function. There was a complex non-linear relationship between PA and age-adjusted SAF score: mean SAF was the highest in sedentary participants (e.g., 0 min/week moderate-to-vigorous physical activity), lowest in those with 150–299 min/week PA, and gradually increasing in participants with higher than 600 min/week PA.ConclusionsWe provide robust reference values for SAF, established in healthy individuals of Western European descent, separately by sex, who have never smoked. Higher levels of SAF are observed in former and current smokers and in people with T2D, CVD, and impaired renal function. The relationship between physical activity and SAF scores is complex, with higher SAF scores demonstrated in sedentary people and those performing a large amount of moderate-to-vigorous physical exercise.